Isolation and characterization of highly lytic bacteriophages against staphylococcus aureus in malaysian sewage water - Tee, Jyng Sheng; Chen, Bihe; Lee, Chin Mei (Journal of Pure and Applied Microbiology, 2024)
Staphylococcus aureus is a pathogen that can cause both minor and life-threatening infection to human. Recently, the emergence of antibiotic-resistant Staphylococcus aureus (MRSA) has become a global public health concern. As an alternative to antibiotics, bacteriophage therapy is receiving increasing attention. Isolation and characterization of more Staphylococcus aureus phages is an important prerequisite for building a large repository of phages that can be used in the future for phage therapy. Here we report the isolation of bacteriophages against S. aureus ATCC 6538, the first of its kind in Malaysia. Twenty phages were isolated and two were examined in detail. These two phages, TJSb3 and TJSb6, were found to be highly lytic and belong to the order Caudovirales and the family Siphoviridae. TJSb3 and TJSb6 have high efficiency of plating (EOP value) of 0.907 ± 0.085 and 0.665 ± 0.114, respectively. These two phages exhibited a broad lytic effect against the 4 different S. aureus strains tested (one of which, S. aureus ATCC 43300, is a MRSA strain). TJSb3 and TJSb6 also have small genome size of 20-30k base pairs, making them smaller than 90% of the S. aureus phages recorded in the NCBI viral genome database. These traits make TJSb3 and TJSb6 very attractive as potential candidates for phage therapy.